Integration of ZnCo2S4 nanowires arrays with NiFe-LDH nanosheet as water dissociation promoter for enhanced electrocatalytic hydrogen evolution. (20th November 2019) - Quan, Biao; Tong, Huamei; Liu, Chenchen; Li, Di; Meng, Suci; Chen, Min; Zhu, Jianjun; Jiang, Deli
Abstract: Developing high-efficiency but nonprecious electrocatalysts for hydrogen evolution reaction (HER) in basic media is of great importance for energy conversion. Bimetallic transition metal sulphide (TMS) nanoarrays have been regarded as promising HER electrocatalyst owing to its high conductivity and synergy of different active sites. However, the reaction kinetic of HER for bimetallic TMS is sluggish probably due to the limited active sites for the dissociation of H2 O molecule. Herein, NiFe-LDH (NFL) nanosheets are anchored on the ZnCo2 S4 (ZCS) nanowire arrays supported on nickel foam (NF) to form core-shell hierarchical ZnCo2 S4 @NiFe-LDH architecture (ZCS@NFL/NF). Resulting from the 3D core-shell architectures and synergy between ZCS and NFL, the ZCS@NFL/NF needs a low overpotential of 110 mV to deliver 10 mA cm −2 for HER in 1 M KOH, which is about 135 mV lower than the bare ZCS/NF and superior to many reported Co-/Ni-based-electrocatalysts. We anticipated that this work could open up an avenue for development of core-shell hierarchical architecture HER electrocatalysts by using LDHs materials as the H2 O dissociation promoter.